Pull-out behavior evaluation of torque-controlled expansion anchors under various installation conditions of concrete - Jin Soo Bang (Elsevier, 2022)
Torque-controlled expansion anchors are widely used as anchoring elements in heavy nonstructural elements. Although the installed torque is not considered a design parameter for determination of anchor strength, it can affect the contact condition between the concrete and anchor as well as the failure mode under tensile load. This study performed pull-out experiments (total 85 specimens) for torque-controlled expansion anchors to evaluate the pull-out behavior under various installation conditions. Experimental results indicated that obtained inflection load and maximum displacement were affected by the installation torque. Concrete splitting failure was affected by pull-out behavior on concrete below critical edge distance. While maximum pull-out loads of M12 and M16 anchor was similar under the same embedment depth, pull-out behavior of the both types of anchors provide different characteristic. Accordingly, these results were analyzed to investigate the influence on anchor strength.